2022
DOI: 10.3389/fcell.2021.784035
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective Effects of Omentin-1 Against Cerebral Hypoxia/Reoxygenation Injury via Activating GAS6/Axl Signaling Pathway in Neuroblastoma Cells

Abstract: Ischemic stroke is characterized by insufficient blood supply to brain tissue and is associated with increased morbidity and mortality in adults worldwide. Growth arrest-specific protein 6 (GAS6) is a vitamin K-dependent protein and is widely expressed in the central nervous system. The biological functions of GAS6 are mediated by the interaction with TAM (Tyro3, Axl and Mertk) receptors, including cell survival and proliferation, immune regulation and apoptosis. Omentin-1, also known as intelectin-1 (ITLN-1),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 34 publications
(40 reference statements)
0
5
0
Order By: Relevance
“…It is reported that low ITLN‐1 level indicates high risk of ischemic stroke (Kazimierczak‐Kabzińska et al, 2020; Lin et al, 2021; Xu et al, 2020). Also, our previous study further demonstrated that ITLN‐1 protects against cerebral hypoxia/reoxygenation injury in N2a cells (Niu et al, 2021). The above evidence denotes that ITLN‐1 has a powerful potential neuroprotection.…”
Section: Introductionmentioning
confidence: 77%
See 1 more Smart Citation
“…It is reported that low ITLN‐1 level indicates high risk of ischemic stroke (Kazimierczak‐Kabzińska et al, 2020; Lin et al, 2021; Xu et al, 2020). Also, our previous study further demonstrated that ITLN‐1 protects against cerebral hypoxia/reoxygenation injury in N2a cells (Niu et al, 2021). The above evidence denotes that ITLN‐1 has a powerful potential neuroprotection.…”
Section: Introductionmentioning
confidence: 77%
“…Passaging was performed once the cell confluence reached approximately 80%. The N2a cells were subjected to serum starvation before the experiment, as described in the previous literature (Niu et al, 2021). To induce oxidative stress injury, the cells were exposed to different concentrations of H 2 O 2 (0.5, 1, 2, and 4 mM) for 4 h. According to cell viability and cell morphology, the most appropriate concentration was selected for subsequent experiments.…”
Section: Methodsmentioning
confidence: 99%
“…13 the occurrence of MACCE (Dong et al 2021;Lin et al 2021;Ma et al 2022;Niu et al 2021;Tan et al 2019;Wang et al 2020;Watanabe et al 2016). As a result, omentin-1 reflected reduced MACCE risk in patients receiving hemodialysis.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…The concentration of omentin-1 is inversely related to the levels of pro-inflammatory cytokines such as IL-6 and TNF-α [ 106 ]. A positive effect of omentin on endothelial function through improvement of the production of nitric oxide [ 107 ], which reduces oxidative stress and apoptosis [ 108 ], has been demonstrated.…”
Section: Anti-inflammatory Adipokines In Obesity and Its Complicationsmentioning
confidence: 99%